Morphological status of assimilated atlas vertebra with occipital bone and its clinical significance - Gopal, Krishna; Choudhary, Alok Kumar; Agarwal, Jolly; Ali, Sadakat (International Journal of Research in Medical Sciences, 2017)
Background: Atlas is the first cervical vertebra. Sometimes there is partial or complete fusion of atlas with basal part of the occipital bone known as assimilation of atlas or atlanto-occipital fusion. It is normally congenital. It may be associated with the constriction of foramen magnum which may compress the spinal cord or brain stem. Methods: The 1000 human dry skulls were selected from the anthropology museum of department of anatomy, GSVM medical college, Kanpur. The age and sex of the skulls were not taken into consideration. The skulls were examined for the bony union between the atlas and skull and other variations in assimilated atlas. Results: Fused atlas with skull was seen in 20 skulls (2.0%). Partial fusion of anterior arch of atlas with the occipital bone was seen in 1 specimen (5%) and in 10% it was found complete fusion. In 10% skulls the posterior arch fused with the occipital bone. Bilateral fusion of transverse process with occipital bone was noted in 2 (10%) specimen. The incomplete foramen transversarium was found in 1 skull (5%) {bilateral} and in 2 skulls (10%), the transverse process was noted without the foramen transversarium {bilateral}. Conclusion: Out of 1000 examined skulls, fusion of atlas with the occipital bone was noted in 20 skulls (2%). The knowledge of incidence of assimilation of atlas and its variations may be helpful for the embryologist, neurosurgeons and orthopedic surgeons.